THE INFLUENCE OF QUALITY PERCEPTION, MULTISENSORY PERCEPTION, AND BRAND REPUTATION ON PURCHASE INTENTION USING TRUST AS MEDIATION ON TIKTOK SHOP - Ramadhaningtyas, Novendra Frida; Kussudyarsana, Kussudyarsana (LPPM Univ. Ibn Khaldun Bogor, 2025)
This research examines the influence of quality perception, multisensory perception, and brand reputation on consumer purchase intention on TikTok Shop, with trust as a mediating variable. The rapidly developing phenomenon of online shopping, especially on social media platforms like TikTok, makes consumer trust a crucial foundation. Although previous studies have highlighted the importance of trust and quality perception, the integration of brand reputation and multisensory elements in influencing purchase intention has rarely been explored in depth. Using a quantitative approach with 177 TikTok Shop user respondents in Surakarta, data was collected through questionnaires and analyzed using SmartPLS 4. The research results show that quality perception and brand reputation have a positive and significant influence on trust. Trust, in turn, also has a positive and significant influence on purchase intention. Furthermore, trust is proven to significantly mediate the relationship between quality perception and purchase intention, as well as between brand reputation and purchase intention. However, multisensory perception does not show a significant influence on trust, and trust is also unable to significantly mediate the relationship between multisensory perception and purchase intention. These findings underscore the vital role of quality and reputation in building trust, which then drives purchase intention in a dynamic e-commerce environment. This research provides practical insights for sellers on TikTok Shop to optimize their marketing strategies by focusing on improving product quality, building a strong brand reputation, and fostering consumer trust.